The Machiavellian Character, Ethical Environment and Personal Cost in Their Impact to Whistleblowing Intention - Arumega Zarefar; Raja Adri Satriawan Surya; Nanda Fito Mela (Politeknik Caltex Riau, 2018)
The objective of this study is to examine the effect of Machiavellian Character, Ethical Environment and Personal Cost to Whistleblowing Intention. This research was directed to all employees who work on SAMSAT Pekanbaru City and Rokan Hulu District. The sampling method that used in this study is purposive sampling. Collecting data of this study using a questionnaire submitted to 130 working in the office of One Stop Roof Administration Unit (SAMSAT) Pekanbaru City and Rokan Hulu District. From questionnaires distributed, 82 questionnaires can be completed and can be processed. Data collected were analyzed with Partial Least Square (PLS). The results of hypothesis testing conclude that: first, Machiavellian nature has influence toward whistleblowing intention with value tcount 3,551 > ttable 1,99. Second, Ethical Environment has effect toward whistleblowing intention with value tcount 2,829> ttable1,99. Third, Personal Cost has impact toward whistleblowing intention with value tcount 4,200> ttable 1,99. The result of the coefficient of determination (R2) is 0,556 which means that the independent variable used in this research affects Whistleblowing Intention of 55,6% while the remaining 44,4% is influenced by other variables not included in this regression model.